Quasi umbilical submanifold of KH-structure manifold - Lal, Shankar (Journal of Experimental Sciences, 2012)
The purpose of the present paper is to study the quasi umbilical submanifold of co-dimension-2 of KH-structure manifold. Hypersurfaces immersed in an almost hyperbolic Hermite manifolds studied by Dube [4]. On GH-structure manifold have been studied by Mishra, R.S. & Singh, S.D. [8]. We have obtained the conditions for this submanifold to be W-Quasi umbilical. The paper is organized as follows quasi umbilical. In section one, introductory part of GF-structure and KH-structure is defined some useful equations. In section two, we prove that the some theorems, definitions and corollaries in quasi umbilical submanifold as well as Nijenhuis tensor. In the end, we have discussed about manifold and quasi umbilical submanifold.